Analysis of Hydraulic Characteristics According to the Cross-Section Changes in Submerged Rigid Vegetation - Lee, Jeongheum; Jeong, Yeon-Myeong; Kim, Jun-Seok; Hur, Dong-Soo (Han-guk haeyang gonghak hoeji (Online), 2022)
Recently, not only Korea but also the world has been suffering from problems related to coastal erosion. The hard defense method has been primarily used as a countermeasure against erosion. However, this method is expensive and has environmental implications. Hence, interest in other alternative methods, such as the eco-friendly vegetation method, is increasing. In this study, we aim to analyze the hydraulic characteristic of submerged rigid vegetation according to the cross-sectional change through a hydraulic experiment and numerical simulation. From the hydraulic experiment, the reflection coefficient, transmission coefficient, and energy dissipation coefficient were analyzed according to the density, width, and multi-row arrangement of the vegetation zone. From numerical simulations, the flow field, vorticity distribution, turbulence distribution, and wave distribution around the vegetation zone were analyzed according to the crest depth, width, density, and multi-row arrangement distance of the vegetation zone. The hydraulic experiment results suggest that the transmission coefficient decreased as the density and width of the vegetation zone increased, and the multi-row arrangement condition did not affect the hydraulic characteristics significantly. Moreover, the numerical simulations showed that as the crest depth decreased, the width and density of vegetation increased along with vorticity and turbulence intensity, resulting in increased wave height attenuation performance. Additionally, there was no significant difference in vorticity, turbulence intensity, and wave height attenuation performance based on the multi-row arrangement distance. Overall, in the case of submerged rigid vegetation, the wave energy attenuation performance increased as the density and width of the vegetation zone increased and crest depth decreased. However, the multi-row arrangement condition did not affect the wave energy attenuation performance significantly.